β-Glucan of Candida albicans Cell Wall Extract Inhibits Salmonella Typhimurium Colonization by Potentiating Cellular Immunity (CD8 + and CD4 + T Cells) - Winarsih,Sri (2019)
Abstract INTRODUCTION: Antimicrobial resistance has been reported in the drugs used for the treatment of typhoid fever. The immunomodulatory substance β-glucan can be used as an alternative therapy as it potentiates host immunity. The aims of this study are to observe the effect of Candida albicans cell wall (CCW) extract towards host immunity (TCD8+ and TCD4+ cells in spleen, intestinal sIgA) and its capacity to kill Salmonella in the intestine and liver of typhoid fever mice models. METHODS: Typhoid fever mice models were created by infecting mice with S. Typhimurium orally. Mice were divided into four groups: the Non-Infected, Infected, CCW (infected mice treated with 300 µg CCW extract/mouse once a day), and Ciprofloxacin groups (infected mice treated with 15 mg/kg BW ciprofloxacin twice a day). RESULTS: Secretory IgA (sIgA) concentrations of mice in the CCW group remained unchanged. However, their TCD4+ and TCD8+ cells increased substantially compared to those in the Non-Infected group. In the Ciprofloxacin group, sIgA concentrations increased markedly compared to those in the Non-Infected and CCW groups; TCD4+ and TCD8+ cells also increased significantly compared to those in the Infected Group, but not significant compared to those in the CCW group. Colonization of S. Typhimurium in the intestine and liver decreased significantly in the CCW and Ciprofloxacin groups compared to that in the Infected group, with the lowest reduction being found in the Ciprofloxacin group. CONCLUSIONS The inhibition of S. Typhimurium colonization by CCW is associated with the increase in TCD4+ and TCD8+ cells.